2014
DOI: 10.1155/2014/323049
|View full text |Cite
|
Sign up to set email alerts
|

Successful Thrombolysis despite Having an Incidental Unruptured Cerebral Aneurysm

Abstract: Purpose. To report a case of successful thrombolysis performed in a patient with an incidental unruptured intracranial aneurysm and review the literature. Case Report. Patient admitted for ischemic stroke due to left posterior cerebral artery occlusion, with an incidental right middle cerebral artery aneurysm, who underwent treatment with tissue plasminogen activator (rtPA) resulting in clinical improvement without complications. Conclusion. The presence of unruptured intracranial aneurysms is considered as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…But the treatment opportunity of interventional embolization is controversial. It has been pointed out that the presence of blood clot and cerebral tissue swelling could affect the expose of aneurysm of some patients with aneurysm rupture, which could increase surgical risks and difficulties, and that symptomatic treatment such as reducing intracranial pressure and controlling disease condition before surgery and performing surgery after peak stage of occurrence of cerebral angiospasm are helpful to patients 16. Performing surgery as soon as possible is also advocated to avoid the deterioration of disease condition 17.…”
Section: Discussionmentioning
confidence: 99%
“…But the treatment opportunity of interventional embolization is controversial. It has been pointed out that the presence of blood clot and cerebral tissue swelling could affect the expose of aneurysm of some patients with aneurysm rupture, which could increase surgical risks and difficulties, and that symptomatic treatment such as reducing intracranial pressure and controlling disease condition before surgery and performing surgery after peak stage of occurrence of cerebral angiospasm are helpful to patients 16. Performing surgery as soon as possible is also advocated to avoid the deterioration of disease condition 17.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous t-PA was recognized as the approved thrombolytic agent for acute ischemic stroke that can improve patients' outcome and resolve their neurological deficits. The main reason for the difficulty of stroke treatment is the narrow time window, which leads to a small proportion of eligible patients to be treated with t-PA (16). The first clinical application of t-PA, with the aim of dose verification, mechanism of action, and safety profile, in stroke thrombolysis, began in early 1990s.…”
Section: Tissue Plasminogen Activator In Stroke: Dosage and Time Windowmentioning
confidence: 99%
“…The budget impact analysis, based on stroke incidence rates and the impact of thrombolysis on society's health, showed that thrombolysis improve society's health, although the quality of life may have a stronger association with age, sex, level of education and post-stroke duration (34)(35)(36). The most serious complication of rt-PA thrombolytic therapy is intracranial hemorrhage (ICH) (16). Based on NINDS trials, ICH could be categorized in two groups: 1) symptomatic ICH, documented with computed tomography (CT) and associated with clinical deterioration; 2) ICH with CT finding and no clinical deterioration (9).…”
Section: Profits and Possible Side Effects Of Tissue Plasminogen Actimentioning
confidence: 99%
“…Some case reports have discussed the safety of applying r-tPA to patients with unruptured intracranial aneurysms [ 8 , 9 ]. In particular, some have demonstrated the bleeding risk of administering r-tPA in patients with unruptured intracranial aneurysm.…”
Section: Introductionmentioning
confidence: 99%